The practical benefits of legal anthropology in achieving social and cultural justice in society - Farkhan Maulana Sidik (Universitas Negeri Yogyakarta, 2025)
This study aims to examine legal anthropology as an interdisciplinary approach that integrates legal studies with anthropology to understand law as a social and cultural product. The primary focus of this research is to explore how legal systems are not merely understood as sets of normative rules, but as socially constructed institutions that reflect the values, practices, and cultural structures of society. The study employs a qualitative methodology using legal ethnography, which involves participant observation, in-depth interviews, and document analysis to investigate legal practices within various local community contexts. The findings identify five major schools of thought in legal anthropology: evolutionism, functionalism, structuralism, symbolic-interpretive, and cognitivism. Each school offers distinct theoretical assumptions and contributes to how law is perceived within society. The study reveals that the existence and operation of law are deeply influenced by cultural contexts and social dynamics in which the law is embedded. Legal anthropology enables analysis of how law is practiced, negotiated, and interpreted by individuals and groups in their everyday lives. The conclusion of this research asserts that legal anthropology provides a critical perspective in developing legal systems that are more adaptive, inclusive, and socially relevant. By understanding law as a living social phenomenon rooted in culture, the anthropological approach offers a valuable framework for designing more just and contextual legal policies, as well as for bridging the gap between normative law and actual legal practice in plural societies.